JADID DRAMAS AND THEIR ETHNOCULTURAL VALUES - Qalandar Rustamov (Journals Park Publishing, 2023)
This article talks about the formation of national ideology and culture in the beginning of the 20th century, the introduction of modern ideas, the struggle to achieve freedom and to have a new school system.
Keywords: History of Turkestan, modern ideas, National ideology, Dramas of ABDULLA AVLONI, Tragedy of life.